Writing for Publication: The Engineers Obligation - Friedstein, Harriet (Engineering Journal, 1986)
The engineering professional has an obligation to the discipline to communicate, either through papers delivered at topical conferences or through journals and magazines. This article describes the advantages and disadvantages of writing for publication. Once the key is established for the need to write for the profession, some basic guidelines are offered for the novice. Suggestions are given on how to get started; how to generate ideas into articles; what to do in the actual writing process from first to final draft. Finally, the author offers some suggestions for turning the draft into a polished manuscript. In our technological society, we need more technically competent writers for the multitudes of journals and magazines that proliferate. Non-fiction informational articles compose the largest percentage of published works today. Should we assume that all these writers are professional journalists? True, some are, but a great many are not. Their interests in technical subjects and their skills in writing have given them a chance to communicate with the reader. However, writing is not to be limited to the journalism majors.